The impact of job satisfaction and organisational commitment on intention to turnover and job performance - Özbenli, Şebnem (My University, 1999)
Bu araştırma iş tatmini ve organizasyona bağlılık'ın işi bırakma niyeti ve iş performansı üzerindeki etkisine netlik kazandırmak amacıyla gerçekleştirilmiştir. Araştırmanın diğer bir amacı da, çalışmanın uygulandığı şirkette halen yaşanan işi bırakma niyetleri ve düşük iş performansı hususunda öneriler ortaya koymaktır. Reklamcılık sektöründeki bir reklam satış şirketinden, gönüllü olarak katılan 66 satış elemanı üzerinde yapılan araştırmada, iş tatmini Minnesota Satisfaction Questionnarie (MSQ), örgüte bağlılık ve işi bırakma niyeti ise bir çok araştırmacının uyguladığı anket soruları incelenip, hazırlanmıştır. İş performansı ise ilgili şirkette halen uygulanmakta olan İş Performansı Değerlendirme Anketi ile ölçülmüştür. 25 soru iş tatmini, 9 soru organizasyona bağlılık, 2 soru işi bırakma niyeti, 7 soru şirket uygulamaları ile ilgili genel maddeleri ve 18 soru performans değerlendirmesini kapsamaktadır. Araştırmanın sonucunda iş tatmini ve örgüte bağlılık işi bırakma niyeti ile ters ilişkili, iş performansı ile doğru ilişkili bulunmuştur. Ayrıca işi bırakma niyeti ve iş performansının organizasyona bağlılıkla, iş tatmininden daha fazla ilişkili olduğu da bulunmuştur.

This study was made to clarify the impact of job satisfaction and organisational commitment on the intention to turnover and job performance. Another aim was to suggest solutions about the problems of the already prevailing intention to turnover and the low level of job performance to the company for which the current study is conducted. In the research conducted on 66 volunteering sales personnel in an advertising sales company in the Advertising sector, job satisfaction is measured on the basis of; Minnesota Satisfaction Questionnaire (MSQ). Organisational commitment and intention to turnover is measured by a questionnaire prepared after analysing the questionnaires conducted by various researchers, and job performance is measured by Job Performance Evaluation Questionnaire currently used by the related company. 25 questions on job satisfaction, 9 on organisational commitment, 2 on intention to turnover, 7 questions on the general items related with organisational practices, and 18 questions related with performance appraisal were asked. The results of the study supported that both job satisfaction and organisational commitment were negatively related with intention to turnover and positively related with job performance. Also it is found out that the relationship of intention to turn over and job performance related with organisational commitment was stronger than their relationship with job satisfaction.
Keywords: İş Tatmini; Personel Yönetimi